Advances in Polaron Physics - Alexandrov, Alexandre S.; Devreese, Jozef T. (Springer Series in Solid-State Sciences,, 2010)
While basic features of polarons were well recognized a long time ago and have been described in a number of review papers and textbooks, interest in the role of electron-phonon interactions and polaron dynamics in contemporary materials has recently gone through a vigorous revival. Electron-phonon interactions have been shown to be relevant in high-temperature superconductors and colossal magnetoresistance oxides, and transport through nanowires and quantum dots also often depends on vibronic displacements of ions. The continued interest in polarons extends beyond physical description of advanced materials. The field has been a testing ground for analytical, semi-analytical, and numerical techniques, such as path integrals, strong-coupling perturbation expansion, advanced variational, exact diagonalization, density-matrix renormalization group, dynamic mean-field, and quantum Monte Carlo techniques. Single and multi-polaron theories have offered a new insight in our understanding of high-temperature superconductivity, colossal magnetoresistance, and the correlated transport through molecular quantum dots. This book reviews some recent developments in the field of polarons, starting with the basics and covering a number of active directions of research.